TERAPI DZIKIR MENURUNKAN KECEMASAN PADA PASIEN PRE OPERATIF DI KAMAR OPERASI RSUD TAMAN HUSADA BONTANG - Jaka Hidayatullah Koswara Putra; Edi Sukamto; Badar (Jurnal Cakrawala Ilmiah, 2023)
Background: Surgery is an invasive procedure carried out by opening or exposing the part of the body to be treated, typically done by making an incision in a specific area of the body. Once the part of the body to be treated is visible, corrective actions are taken and it will be closed by stitching the wound in that area. Objective : To determine the influence of Dhikr therapy on preoperative patient anxiety in the operating room of RSUD Taman Husada Bontang in 2023. Method: This research is a quantitative study using a pre-experiment design with a one-group pre-post test design without control approach. The sample in this study consisted of 33 preoperative patients in the inpatient rooms of Edelwis, Boungenville, and Seruni, selected through non-probability sampling with a consecutive sampling method using the Wilcoxon test. Results: The Wilcoxon test analysis yielded a p-value of 0.001 ≤ 0.05, which allows the conclusion that there is a significant influence of Dhikr therapy on preoperative patient anxiety in RSUD Taman Husada Bontang 2023. Conclusion: For patients about to undergo surgery, Dhikr therapy with recitation of tasbih, tahmid, and takbir phrases, each repeated 33 times or adjusted to the patient's dhikr habit for 10-15 minutes, can reduce the level of anxiety